1999
DOI: 10.1097/00003446-199910000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Tympanic Pressure Gradients and Otoacoustic Emissions

Abstract: The progressive attenuation of the OAE response and the concomitant shortening of the OAE response latencies were observed during a combination of altered middle and inner ear pressure. Although the middle and inner ear influence cannot be separated we suggest, based on our findings, that the shortening of latencies may partly be caused by inner ear pressure changes and stiffening of the labyrinthine membranes. Further studies are needed to more specifically clarify the relative contribution of the tympanic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
3
15
1
Order By: Relevance
“…Published studies [12][13][14][15][16][17][18][19][20] have shown that external and middle ear features may interfere doubly on recordings of emissions. Although the sealing condition of buds on the external acoustic meatus and the meatus itself may cause interferences, more emphasis has been given to the role of the middle ear.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies [12][13][14][15][16][17][18][19][20] have shown that external and middle ear features may interfere doubly on recordings of emissions. Although the sealing condition of buds on the external acoustic meatus and the meatus itself may cause interferences, more emphasis has been given to the role of the middle ear.…”
Section: Introductionmentioning
confidence: 99%
“…A system combining TEOAE measurement and tympanometry should have the possibility to compensate an abnormal (negative) middle ear pressure. Once pressure equilibration is achieved, the tympanic membrane, maybe also the labyrinthine window membranes and basal membrane becomes more relaxed and sound transmission should improve [7]. This could lower the number of false positives in referred patients and could make an important contribution to the practical application of TEOAEs.…”
Section: Discussionmentioning
confidence: 99%
“…6 The TEOAE has a correlation response !70% and a S/N ratio !6 dB for at least 3 frequency bands Def. 7 The TEOAE has a correlation response !85% and a S/N ratio !6 dB for at least 2 frequency bands Def. 8 The TEOAE has a correlation response !70% and a S/N ratio !6 dB for at least 2 frequency bands Def.…”
Section: Subjectsmentioning
confidence: 99%
“…A pressure difference between the outer and the middle ears can be induced by altering the atmospheric pressure in a pressure chamber (Richter et al 1994;Konradsson et al 1999) or by changing the air pressure in the ear canal using a probe placed in the subject's ear (Robinson & Haughton 1991;Osterhammel et al 1993;Plinkert et al 1994). Frequency-dependent changes in evoked otoacoustic emissions (EOAEs) are found when the pressure in the ear canal is increased or decreased (Robinson & Haughton 1991;Osterhammel et al 1993;Plinkert et al 1994;Richter et al 1994;Konradsson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Frequency-dependent changes in evoked otoacoustic emissions (EOAEs) are found when the pressure in the ear canal is increased or decreased (Robinson & Haughton 1991;Osterhammel et al 1993;Plinkert et al 1994;Richter et al 1994;Konradsson et al 1999). The introduction of positive pressure to the ear canal, which displaces the tympanic membrane inward, has more of an effect on EOAEs than the introduction of negative pressure (Robinson & Haughton 1991;Plinkert et al 1994).…”
Section: Introductionmentioning
confidence: 99%